A comparative analysis of English for academic purposes teachers’ interactive metadiscourse across the British and Chinese contexts - Wu, Xinxin; Yang, He (Frontiers in Psychology, 2022)
This exploratory research compares the interactive metadiscourse use by native English speaking EAP writing teachers in the UK and their non-native counterparts in the Chinese contexts. The analysis is based on a self-compiled corpus, including two sub-corpora, which were composed of instructor contributions to classroom discourse: 8 sessions of EAP lessons from the Chinese context, and 8 sessions of EAP lessons from the British context. Adopting Hyland’s (2005; 2019) interpersonal model of metadiscourse, the two sub-corpora were compared to examine the similarities and differences in their use of interactive metadiscourse. Findings of the comparative analysis reveal that EAP teachers from both contexts rely heavily on transition markers and frame markers to organize their teaching, but differ in particular linguistic realizations. This may indicate the impact of a range of factors such as logical preferences, development order of acquisition, discourse community and speech community, on teachers’ interactive metadiscourse strategies. The paper concludes with a few implications for metadiscourse research in spoken academic genres.